Rising burden of pancreatic cancer in China: Trends, drivers, and future projections - Zhouwei Zhan; Xiuhui Zheng; Shaohua Xu; Hanchen Zheng; Lina Zheng; Jie Wang; Hui Lin; Jiami Yu; Zengqing Guo; Bijuan Chen (PLoS ONE, 2025)
Pancreatic cancer is one of the most lethal malignancies globally, with increasing incidence and mortality trends. In China, the disease burden has escalated over the past three decades, yet comprehensive national assessments remain limited. This study aims to evaluate the long-term trends, driving factors, and future projections of pancreatic cancer burden in China from 1990 to 2021. Data on incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) were extracted from the Global Burden of Disease (GBD) Study 2021. Temporal trends were analyzed using Joinpoint regression and age-period-cohort models, while decomposition analysis quantified the contributions of population aging, growth, and epidemiological change. Bayesian age-period-cohort (BAPC) models were applied to project disease burden trends through 2030. In 2021, pancreatic cancer accounted for 118,665 new cases and over 2.9 million DALYs in China, with a significantly higher burden among males. Age-standardized rates of incidence, prevalence, and DALYs increased markedly between 1990 and 2021, outpacing global trends. The burden was concentrated in older age groups and driven primarily by years of life lost. Joinpoint regression identified periods of accelerated increase after 2015. Age-period-cohort analysis revealed that disease burden rises sharply after age 50 and is highest among more recent birth cohorts. Decomposition analysis showed that population aging and epidemiological transitions were the main contributors to increased burden. Projections using BAPC models indicate that incidence, prevalence, and DALY rates will continue to rise through 2030. The burden of pancreatic cancer in China has increased substantially over the past three decades and is projected to rise further. These findings highlight the need for intensified public health interventions focused on prevention, early detection, and effective treatment strategies.